YOUTH UNEMPLOYMENT AND NIGERIA'S SUSTAINABLE DEVELOPMENT - Bashir Abdullahi; Labajirge Bedan Silas; Ibrahim Idris Pindiga (International Studies Journal)
This study examined the menace of youth unemployment in Nigeria by focusing on factors responsible for the menace as well as its destructive consequences on Nigeria’s existence and development. The study relied on the secondary data while content analysis was employed in analyzing the gathered data. Marxist Theory of Unemployment was used as a framework of analysis in this study. The study discovered that the menace of unemployment among youths in Nigeria has significantly affected Youth population psychologically with severe consequences on Nigeria’s survival as a country as well as retarding her development aspiration. Youth Unemployment led to Youth involving in Destructive activities such as militancy, insurgency, banditry, political thuggery and other crimes in the society. It is recommended that government should focus its attention to the quality of education so as to produce employable graduates, anti-corruption agencies be given full independence to fight corruption, there should be steady supply of electricity in order to enable industries operate which in turn can generate employment to the teeming youth.